Gaya Hidup dan Kejadian Hipertensi pada Perawat Rawat Inap: Lifestyle and Hypertension Incidence among Inpatient Nurses - Zulfia Khoyrotun Nisa; Feri Catur Yuliani; Rizal Fajri (Universitas Ngudi Waluyo, 2026)
Inpatient nurses have a high risk of experiencing health problems due to heavy workloads, high stress levels, and irregular shift work patterns. These conditions often trigger unhealthy lifestyle changes, such as poor diet, lack of physical activity, and sleep disturbances, which are major risk factors for hypertension. This study aimed to determine the relationship between lifestyle and the incidence of hypertension among inpatient nurses at RSU Nurussyifa Kudus. This was a quantitative study with an analytical design using a cross-sectional approach. The sample consisted of 43 inpatient nurses selected through a total sampling technique. The research instruments included a lifestyle questionnaire and a blood pressure observation sheet, while data analysis was performed using the Spearman Rank statistical test. The results showed that the majority of nurses had an unhealthy lifestyle, accounting for 40 respondents (93.0%), and most experienced stage 1 hypertension, totaling 23 respondents (53.5%). Based on the Spearman Rank statistical test, a p-value of 0.019 ( ) was obtained, indicating a significant relationship between lifestyle and the incidence of hypertension among inpatient nurses at RSU Nurussyifa Kudus. Hospital management is advised to establish occupational health and safety (OHS) promotion programs to mitigate work-related health risks.Inpatient nurses have a high risk of experiencing health problems due to heavy workloads, high stress levels, and irregular shift work patterns. These conditions often trigger unhealthy lifestyle changes, such as poor diet, lack of physical activity, and sleep disturbances, which are major risk factors for hypertension. This study aimed to determine the relationship between lifestyle and the incidence of hypertension among inpatient nurses at RSU Nurussyifa Kudus. This was a quantitative study with an analytical design using a cross-sectional approach. The sample consisted of 43 inpatient nurses selected through a total sampling technique. The research instruments included a lifestyle questionnaire and a blood pressure observation sheet, while data analysis was performed using the Spearman Rank statistical test. The results showed that the majority of nurses had an unhealthy lifestyle, accounting for 40 respondents (93.0%), and most experienced stage 1 hypertension, totaling 23 respondents (53.5%). Based on the Spearman Rank statistical test, a p-value of 0.019 ( ) was obtained, indicating a significant relationship between lifestyle and the incidence of hypertension among inpatient nurses at RSU Nurussyifa Kudus. Hospital management is advised to establish occupational health and safety (OHS) promotion programs to mitigate work-related health risks.